PROPAGATION OF LOCALLY ISOLATED BACILLUS THURINGIENSIS (CAMB 3-023) FOR THE PRODUCTION OF SPORE-CRYSTAL PROTEIN IN SHAKE FLASK (Biological Sciences - PJSIR, 2002)
The shake flask cultural conditions were optimized for the production of spore/crystal protein by locally isolated Bacillus thuringiensis  strai n  CAME 3-023.   Of all the culture media tested , Corn  Steep liquor medium  with the addition  of  MnS0 and CaC12 1gave highly  encouraging  results  of spore counts (l .8X108/ml), crystal protein  yield  (42  mg    g· 4dry  mass) and also maximum dry cell mass (3.9 g t\ The final pH of the fermented mash was alkaline (9.0), 72 h after inoculation with vegetative cells.